2023
DOI: 10.1111/apa.16674
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding rates fell in an Italian baby friendly hospital during the 2020 COVID‐19 pandemic year and difficulties increased

Abstract: The World Health Organisation (WHO) and the United Nations Children's Fund recommend that mothers start breastfeeding within 1 h of birth and exclusively breastfeed for up to 6 months of age. 1,2 To promote breastfeeding, they support the Ten Steps to Successful Breastfeeding as a part of the Baby Friendly Hospital Initiative (BFHI).This includes support for mothers, help in initiating and continuing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The study from Italy cited above had nearly the same results concerning the rate of breastfeeding at discharge in VLBW infants (73.3% vs. 72.7%) 17 . Studies analysing healthy neonates found lower breastfeeding rates, more breastfeeding difficulties, and increased rates of mixed feeding during the pandemic 15 …”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The study from Italy cited above had nearly the same results concerning the rate of breastfeeding at discharge in VLBW infants (73.3% vs. 72.7%) 17 . Studies analysing healthy neonates found lower breastfeeding rates, more breastfeeding difficulties, and increased rates of mixed feeding during the pandemic 15 …”
Section: Discussionmentioning
confidence: 64%
“…17 Studies analysing healthy neonates found lower breastfeeding rates, more breastfeeding difficulties, and increased rates of mixed feeding during the pandemic. 15 The unaltered duration of MOM provision, feeding type and breastfeeding rates may be linked to our visiting policy right from the start of the pandemic. Mothers were never regarded as visitors but as accompanying persons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With increasing evidence, the recommendations and guidelines of many societies like the "German Society for Obstetrics and Gynecology" (DGGG), the "German Society for Perinatal Medicine" (DGPM), the "National Breastfeeding Committee Germany" (NSK) and the "society for neonatology and pediatric intensive care medicine" (GNPI) in Germany have been adapted accordingly and have thus led to reliable advisory bases for medical personnel and parents [14,15]. There are differing reports in breastfeeding behavior (increased, decreased, stayed constant ) in the literature [16][17][18]. One of the most important factors affecting breastfeeding rates was the acute/acquired maternal SARS-CoV-2 infection severity.…”
Section: Introductionmentioning
confidence: 99%